Subhu’l-aʿşâ fî sınâʿati’l-inşâ - 880-01 el-Kalkaşendî, 1355-1418. (Beyrut)
14 cilt (1. c. 576 sayfa ; 2. c. 535 sayfa ; 3. c. 626 sayfa ; 4. c. 501 sayfa ; 5. c. 494 sayfa ; 6. c. 584 sayfa ; 7. c. 456 sayfa ; 8. c. 415 sayfa ; 9. c. 440 sayfa ; 10. c. 482 sayfa ; 11. c. 444 sayfa ; 12. c. 495 sayfa ; 13. c. 403 sayfa ; 14. c. 461 sayfa)